2004
DOI: 10.1099/ijs.0.02858-0
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma ovis comb. nov. (formerly Eperythrozoon ovis), an epierythrocytic agent of haemolytic anaemia in sheep and goats

Abstract: Eperythrozoon ovis, an erythrocytic agent that causes haemolytic anaemia in sheep and goats, occurs worldwide and is currently thought to be a rickettsia. To determine the relationship between this agent and other haemotrophic bacterial parasites, the 16S rRNA gene of this organism was sequenced. Phylogenetic analysis revealed that this wall-less bacterium is not a rickettsia, but a mycoplasma. This mycoplasma is related closely to several other uncultivated, epierythrocytic mycoplasmas that comprise a recentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
78
1
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 34 publications
(44 reference statements)
1
78
1
6
Order By: Relevance
“…Previously known as "Eperythrozoon ovis," the organism was reclassified as M. ovis based upon 16S rRNA gene sequence analysis (17). The organism attaches to erythrocytes and causes "ill thrift," hemolytic anemia, and occasionally icterus, hemoglobinuria, and mortality in lambs (20,24).…”
Section: Case Reportmentioning
confidence: 99%
“…Previously known as "Eperythrozoon ovis," the organism was reclassified as M. ovis based upon 16S rRNA gene sequence analysis (17). The organism attaches to erythrocytes and causes "ill thrift," hemolytic anemia, and occasionally icterus, hemoglobinuria, and mortality in lambs (20,24).…”
Section: Case Reportmentioning
confidence: 99%
“…A PCR protocol for kappa-casein, gene-specific for ruminants, was performed in all samples to verify the presence of amplifiable DNA (Otaviano et al, 2008; Table 1). The PCR assay for M. ovis detection was performed as described (Neimark et al, 2004). A positive control for M. ovis from a naturally infected white-tailed deer (Odocoileus virginianus) was used in all reactions; water was used as negative control.…”
mentioning
confidence: 99%
“…Recently, phylogenetic analysis of 16S rRNA gene sequences from several of these bacteria has demonstrated that these uncultivated wall-less bacteria are not rickettsia, but instead are mycoplasmas (Rikihisa et al, 1997;Neimark & Kocan, 1997;Neimark et al, 2001Neimark et al, , 2002b. In addition, several new haemotrophic Mycoplasma species have been identified in wild and domesticated animals (Messick et al, 2002;Neimark et al, 2002bNeimark et al, , 2004). Here we show that E. coccoides…”
mentioning
confidence: 99%